Pengembangan Media Pembelajaran Interaktif Berbasis Visual untuk Menstimulasi Perkembangan Kognitif Anak Usia Dini - Rini Fitriyani; Sukma Erita; Inaya Olivianita (BOCAH: Borneo Early Childhood Education and Humanity Journal, 2026)
Cognitive development is an important aspect that needs to be stimulated during early childhood. However, the use of conventional learning media often makes children less active and less interested in learning activities. This study aimed to develop a feasible, visually based interactive learning medium to stimulate the cognitive development of young children at TK Kehidupan Efhaluy Tenggarong. The study employed a Research and Development (R&D) approach using the ADDIE model, which comprises Analysis, Design, Development, Implementation, and Evaluation stages. A descriptive qualitative approach was used. Data were collected through observation, interviews, documentation, and validation sheets completed by media and material experts. The results showed that the developed visual-based interactive learning medium received feasibility scores of 92% from the material expert and 93.25% from the media expert, placing it in the highly feasible category. The teacher responded positively to the ease of using the medium in the learning process, while children showed good enthusiasm, attention, and engagement during learning activities. Furthermore, the medium helped children recognize colors, shapes, and objects, as well as engage in simple problem-solving activities. Therefore, the visual-based interactive learning medium is considered a feasible instructional tool to support cognitive development in early childhood education.